3D interconnects and multi-module integrated surface electrode ion trap for scalable quantum information processing - Zhao, Peng (Nanyang Technological University, 2022)
Among the various physical systems for quantum bit (qubit) implementation, trapped ion has drawn significant attention due to its long coherence time (in the second range) and high gate fidelity (>99.99% for single qubit gate). After years of careful development, the ion trap, from mechanically assembled linear trap to lithography-defined surface electrode ion trap, is compatible with CMOS fabrication, which opens the door for the high-resolution, high-repeatability and large-scale ion trap manufacturing. To date, the number of fully connected ion qubits in state-of-the-art ion trapping devices is ~10. However, to scale close to or even beyond the noisy intermediate-scale quantum regime (NISQ, ~100 ions), some challenges remain. One such challenge is to maintain the delicate control of multiple components over individual ion with increasing ion number. In such context, this thesis is committed to boost the scalability of ion trap by integrating advanced 3D interconnects (e.g., through silicon via) and other functional modules (e.g., silicon photonics and multilayer metallization). 3D interconnects are integrated in the half space underneath surface electrode, to replace conventional wire bonding that extends out of the surface. Silicon photonics (grating coupler and waveguide) in place of bulk optics and lenses are used for on-chip light routing and emission. Multilayer metallization is used to maintain the overall RF performance and enable high-density interconnection where necessary. Firstly, surface electrode ion traps on different substrates (namely high resistivity silicon, silicon with grounding plane and glass) are designed and fabricated. Standard CMOS back-end-of-line fabrication process on 12-inch wafer platform is employed. The electrical performances of different traps are compared in terms of leakage current (I-V), parasitic capacitance (C-V), on-chip RF loss (S-parameter) and post-packaging resonance. Though the leakage (at the order of 10-8 A) between neighboring electrodes is relatively high, ion trap on glass substrate demonstrates extremely small capacitance (<1 pF) and low RF loss (insertion loss of <0.05 dB at RF frequency of 50 MHz), as compared to the silicon counterparts. This is mainly due to excellent insulation property of glass. Following that, ion trapping test is performed on the glass trap and ions are successfully confined with an averaged lifetime of ~30 minutes (compatible with the 10-11 mbar vacuum level (10-13 Pa)). To simultaneously leverage the dielectric property of glass and the microfabrication compatibility of silicon, the integration of silicon ion trap and glass interposer is performed, between which TSV is used to build the vertical interconnection. Due to the incorporation of TSV, the original wire bonding pads as well as the connection circuits on the surface electrodes can be eliminated. As a result, the form factor of TSV integrated trap is reduced by ~10 times. Correspondingly, the parasitic capacitance between neighboring electrodes is reduced from >24 pF to 3 pF. Similarly, the insertion loss of TSV integrated trap drops to 0.11 dB, in sharp comparison to the previous traps on silicon substrates (up to 2.4 dB). Analytical models are built to respectively characterize the electrode capacitance and overall power loss, and a good agreement is achieved between the model and the measurement result. In addition, since TSV is located in the half space underneath the surface electrodes, the electrodes geometry design is enabled with high flexibility. Meanwhile, the laser obstruction issue due to the stick-out bonding wires has been resolved. In terms of the ion trapping performance, both the heating rate (17 quanta/ms for an axial frequency of 300 kHz) and the lifetime (~30 minutes) of TSV trap are comparable with non-cryogenic traps of similar dimensions. Moreover, a customized CPGA with patterned redistribution layer is used to locate TSV integrated trap directly in the absence of glass interposer, facilitating high-efficiency thermal management and upgrading the packaging flexibility. At the next stage, the co-integration of other functional modules such as silicon photonics and multilayer metallization with TSV trap is investigated. In silicon photonics module, waveguide and grating coupler are on-chip introduced in place of bulk optics to achieve localized light routing and emission. In multilayer metallization module, as a first step, a grounding plane is incorporated into TSV trap to shield the silicon substrate from RF signal, in which specific windows are patterned onto the plane to accommodate TSV and allow the transmission of lights. The compatibility between TSV/multilayer metallization and waveguide/grating coupler for electrical and optical (E/O) signal routing is demonstrated. The preliminary test result based on wafer frontside shows that a ~40% capacitance reduction is achieved, and the insertion loss further drops to 0.06 dB, close to the performance of glass trap. In addition, the simulation results on photonics components indicate that an overall coupling efficiency of <30 dB is obtained from the input fiber to the ion through the photonics circuit. However, the measured power loss for light with wavelength of 1092 nm is as high as 50 dB. The deviation between the simulation and measurement is largely due to the fabrication imperfection and the resultant sloped grating coupler profile. This thesis focuses on the scalability enhancement of ion trap by integrating TSV, silicon photonics and multilayer metallization into conventional ion trap. The results are promising and pave the way for the future large scale quantum computing based on trapped ion.